Word problem solving skills as determinant of mathematics performance for non-math major students / Shahida Farhan Zakaria ... [et al.] - Zakaria, Shahida Farhan; Nasaruddin, Norashikin; Abd Rahim, Mas Aida; Bosli, Fazillah; Kor, Liew Kee (2021)
Word problem in mathematics frequently leads some students to a challenge as it involves a few strategies to solve the statement. Students are required to read and understand the text of the questions, identify the given information and quantities, transform the information into notation and equation, and finally solve the problem. In order to see the performance of non-major math students in solving mathematical problem, investigation was done in this study. This study took place at one of the universities in Northern Malaysia with 122 respondents of semester one non-math major students from different programs. The methods used were the test of independence and logistic regression in part of seeing at the factors of problem-solving strategies as a whole. These factors were used to investigate if they are related to the performance of the students in mathematics. The results indicated that students who understood the word problem by identifying the correct information and students who prepared problem-solving strategies before answering the questions were three times more likely to be successful in mathematics.